Analytical Note: Study of Water Transfer Plans for Supplying Drinking Water to Mashhad Urban Area from Domestic Sources - Mahbobeh Farzandi (آب و توسعه پایدار)
This study examines the water supply challenges in Mashhad urban area and after-transfer projects. The status of Mashhad Plain's water resources, the decreasing share of dams in supplying the city's drinking water, and the increasing reliance on groundwater extraction have prompted authorities to consider water transfer projects. These projects have been thoroughly analyzed in short-term, mid-term, and long-term perspectives. The water transfer projects from Hezar Masjed and the Oman Sea have been introduced as the most significant ongoing initiatives, along with discussions on some of their environmental and social challenges. The gap between water resources and consumption in Mashhad Plain and the overlooked issues in the Oman Sea water transfer project—such as the focus on structural solutions while neglecting demand management, ambiguity in project financing, the role of the private sector and its impact on national security, and the necessity of social participation in water consumption management—have been addressed. Finally, strategies for water resource management have been proposed, including governance system reforms, increasing stakeholder participation, establishing trust-building mechanisms, integrated water resource management, and implementation of innovative demand management approaches. These include water markets, enhancing groundwater recharge, reducing agricultural water consumption, wastewater treatment, and artificial aquifer recharge.